2017
DOI: 10.1111/pce.13096
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation tolerance in Physcomitrella patens: Rate of dehydration and the involvement of endogenous abscisic acid (ABA)

Abstract: The moss Physcomitrella patens, a model system for basal land plants, tolerates several abiotic stresses, including dehydration. We previously reported that Physcomitrella patens survives equilibrium dehydration to −13 MPa in a closed system at 91% RH. Tolerance of desiccation to water potentials below −100 MPa was only achieved by pretreatment with exogenous abscisic acid (ABA). We report here that gametophores, but not protonemata, can survive desiccation below −100 MPa after a gradual drying regime in an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 47 publications
4
36
2
Order By: Relevance
“…ABA plays key roles in mosses' stress tolerance (Beckett, 1999;Beckett, Csintalan, & Tuba, 2000;Bhyan et al, 2012;Mayaba, Beckett, Csintalan, & Tuba, 2001;Nagao et al, 2005;Xiao, Yobi, Koster, He, & Oliver, 2018). Our results show that stresses induced sharp increases in ABA contents in both species, in accordance with previous studies (Kohli et al, 2013;Xiao et al, 2018).…”
Section: Phytohormone Regulationsupporting
confidence: 91%
“…ABA plays key roles in mosses' stress tolerance (Beckett, 1999;Beckett, Csintalan, & Tuba, 2000;Bhyan et al, 2012;Mayaba, Beckett, Csintalan, & Tuba, 2001;Nagao et al, 2005;Xiao, Yobi, Koster, He, & Oliver, 2018). Our results show that stresses induced sharp increases in ABA contents in both species, in accordance with previous studies (Kohli et al, 2013;Xiao et al, 2018).…”
Section: Phytohormone Regulationsupporting
confidence: 91%
“…Physcomitrella patens is classified as inducibly desiccation tolerant, as exogenous ABA induces DT in protonemata (Oldenhof et al ) and gametophores (Koster et al ). Recent studies have also shown that very slow dehydration of P. patens gametophores, but not protonemata, can induce DT (Greenwood and Stark , Xiao et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Greenwood and Stark () determined that slow drying over a 150‐h period at high humidity could induce DT in gametophores of P. patens , as measured by improved survival and photosynthetic capacity. A recent study by Xiao et al () also demonstrated that gametophores, but not filamentous protonemata, can survive equilibration to water potentials below −100 MPa following a drying regime that features an initial phase with a slow rate of water loss.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations